Through the Ages of Life: Rabindranath Tagore -- Son, Father, and Educator (1861-1941) - M. Banerjee, Swapna (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2017)
Research Framework: This essay attempts to reclaim Rabindranath Tagore (1861-1941), the “Myriad-Minded Man” from colonial India, through his “ages of life” – as a son, father, and educator – and his conceptualization of an alternate education and masculinity. Tagore’s critique of colonial education, his experiments with institutions, and his curriculum emphasizing arts and moral aesthetics over muscular nationalism challenged the dominant culture of masculinity. His paternalism embraced a “manliness” privileging moral and spiritual sustenance over economic and political considerations.Objectives: By focusing on Rabindranath Tagore, an iconic figure of Indian modernity, the essay attempts to demonstrate the tangled relationship between his domestic reality and his public commitment to social justice and pedagogy. Methodology: It deploys the method of contextualized textual analysis by examining a variety of literary sources -- personal narratives, correspondence, lectures, and essays. Results: Foregrounding the importance of family in its enabling and restrictive capacities, the essay explores connections between one family’s life and the Bengali understanding of age, gender, and class in late colonial India. Conclusions: The essay contends that Tagore’s position as a biological father and the transference of his affective concern to a larger body of children, in whom he inculcated a new sense of freedom, were inflected with an alternate sense of masculinity.Contribution: The essay contributes to our understanding that the role of “fathers,” biological and metaphorical, attained heightened significance among the educated, affluent community in colonial Bengal. An examination of the interminable connection between Tagore’s personal and public life disrupts the separation between the home and the world and establishes the centrality of the domestic in Indian nationalist politics. As a father and a reformer, Tagore challenged existing notions of masculinity through his reformed and secular model of education.